Relevansi Pemikiran Ekonomi Sosialisme Islam H.O.S. Tjokroaminoto Dalam Konsep Ke-Indonesiaan - Cahyani, Maya Septi; Hasan, Asyari (ITB AAS INDONESIA Surakarta, 2024)
The socialist movement is conceptualized to fight oppression and demand justice among human beings. Islam as a religion that has values applicable to all humans and is valid at all times, is considered a teaching capable of providing solutions to problems that occur in people's lives. Based on this, Islamic thinkers and movement fighters in Indonesia studied and developed, one of which was H.O.S. Tjokroaminoto. The method used by the author in this journal is library research, which is collecting data contained in the literature, be it books, journals, and others. The nature of the research used is qualitative, namely in the form of sentences and relying on creative interpretations from the researcher. The data analysis process was carried out by summarizing, selecting the main things so that a clear picture of the theme raised could be obtained. The results of this study reveal that H.O.S. Tjokroaminoto about Islamic socialism aims to create prosperity in people's lives. H.O.S. Tjokroaminoto’s economic thinking about Islamic socialism has relevance in the Indonesian context, which is in accordance with the ideals of the Indonesian people contained in the 1945 Constitution.